Dr Hashimoto and the discovery of autoimmune hypothyroidism - Kustrimovic, Natasa; Fazzino , Gaia Francesca Maria; Ghirardello, Claudia; Mariani, Ilaria; Piantanida, Eliana; Tanda, Maria Laura; Gallo, Daniela; Mortara, Lorenzo (Medicina Historica, 2023)
Hashimoto’s disease also known as Hashimoto’s thyroiditis (HT), is one of the most common autoimmune diseases involving the thyroid gland. HT that it is an organ-specific autoimmune disorder characterized by immune cell infiltration into thyroid tissue and thyroid-specific autoantibodies, causing thyroid gland destruction and, eventually, hypothyroidism which is the common clinical manifestation. The discovery of HT was a significant step in the history of medicine and paved the way toward the discovery of autoimmunity and endocrine disorders. HT was discovered by Dr Hakaru Hashimoto over 100 years ago. Surprisingly, it took several decades to be recognised as separate disease and acknowledged as a discovery of Dr Hashimoto. Herein, we summarize what is known of Dr Hashimoto biography and his discovery in order to shine a light on one of the most important discoveries linked to the thyroid disease and autoimmune disorders as well.